High-altitude hypoxia. A challenging strain targeting cellular redox homeostasis - Magalhães,José (2008)
After putting forward some evidence of hypobaric hypoxia as a particular stimulus causing systemic, tissue and cellular challenging strains, the present short review is focused on the current findings relating the reasoning of increased tissue generation of reactive oxygen and nitrogen species (RONS) when humans and animals organisms are exposed to high-altitude environments. In contrast to earlier concepts, hypobaric hypoxia-induced decreased physiological oxygen availability seems to be a prompt condition to cellular loss of redox homeostasis resulting in increased oxidative stress, which does not further augment upon reoxygenation. The apparently paradoxical condition of hypoxia-induced free radical production is regulated by very particular and specific cellular mechanisms, being mitochondria special sources and targets of RONS as well as critical organelles related to cellular death mediated by apoptosis.